KNOWLEDGE AND LAWS OF EDUCATIONAL DEVELOPMENT REGULARITIES AS THE MAIN SUBJECT RESEARCH OF PEDAGOGY (Pedagogy of Higher and Secondary Education, 2004)
The article deals with the attempts of the author to сlassify the laws and regulations of the development of thenational educational and upbringing systems of the Ukrainian фтвneighbouring peoples who for a long time lived under the сonditions of absence of state.